STRATEGI BRAND EQUITY DAN BRAND POSITIONING DALAM MENGATASI PERSEPSI HARGA TINGGI PADA PRODUK BATIKTA DI BALIGE - Rivaldo Simangunsong; Bram Saut Tio Parulian Siregar; Ruth Claudya Sitorus; Grace Vera Hutapea; Mariana Simanjuntak (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the strategy of strengthening brand equity and brand positioning to address the issue of high price perception on BatikTa Balige, a cultural-based local fashion brand from North Sumatra. Many consumers perceive BatikTa’s products as too expensive compared to batik from other regions, creating a gap between the value offered by the brand and the value perceived by the market. The purpose of this research is to analyze how brand equity, brand positioning, and perceived value influence consumers perceived price, as well as how perceived price affects purchase intention. This study adopts a quantitative approach with descriptive and associative methods, involving 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using SPSS through validity testing, reliability testing, normality testing, and regression analysis. The results show that all research instruments are valid and reliable, with Cronbach’s Alpha values exceeding 0.70. Furthermore, the findings reveal that brand equity, brand positioning, and perceived value significantly influence perceived price, while perceived price has a positive effect on purchase intention. These results indicate that strengthening brand identity, communicating cultural value, and establishing a clear and consistent brand positioning can help reduce negative price perceptions and increase consumer willingness to pay. Overall, the study concludes that an integrated branding strategy is essential for enhancing BatikTa’s competitiveness in the local and national fashion markets.